Design of absorptive frequency selective surface with good transmission at high frequency. Issue 12 (1st June 2015) - Chen, Qiang; Chen, Liang; Bai, Jiajun; Fu, Yunqi
Abstract : An absorptive frequency selective surface with a wide absorptive property over the low band and a good transmissive property at high frequency is designed. The transmission of high frequency is realised by putting a choke structure into the element to control the current distribution. Its −10 dB absorption band is from 2.8 to 8.3 GHz and the transmission band is at 9.7 GHz with insertion loss <0.5 dB. Numerical and experimental results are given.